The Social Cultural Education in The Qur'an Perspective - Hilmi Mizani (Program Studi Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2020)
Social and cultural changes in society are increasingly challenging and demanding along with the times marked by developments in technology and communication. However, so that every challenge and change does not lead to setbacks and shapes human behavior to positive values, the value of human hedonism must be bound by positive values. This study aimed to analyze the positive values ​​contained in the Holy Qur'an and al-Hadith. The literature review method has been used in this study to produce socio-cultural changes with thematic studies in the Koran contained in Surah QS al Hujurat: 13, Q.S.Al Qur'an S.Ar Ra'ad: 11, Q.S. Al A'raf: 34, Qur'an S. Ali Imran: 110, QS. Al A'raf: 96, QS. Al Maidah: 8, Qur’an S. Al-‘Asr: 3, Q.S.Al Baqarah: 22, QS. On Tour: 21, QS. Arrum: 41, QS. Joseph: 55) and QS.Hud: 37. The conclusion of socio-cultural education with thematic studies is that every change and development will be followed by other changes, but these changes lead to constructive and positive things, and the direction depends on the belief of each party. individual and collective society.